The route to the development of basal stem rot resistance in oil palm (Elaeis guineensis) via the discovery of lignin degradation process in the pathogen Ganoderma boninense - Joon Sheong Tan,; Yang Ping Lee,; S. Sulaiman,; L. Camus-Kulandaivelu,; C. Klopp,; M. Merciere,; F. Breton,; T. Durand-Gasselin,; S.S.R. Syed Alwee (International Society for Horticultural Science, 2024)
Although the oil palm (Elaeis guineensis) is the oil crop bearing the highest oil yield ha-1 in South-East Asia, it is facing a deadly disease, the basal stem rot (BSR) which is caused by Ganoderma boninense a fungus found commonly in the soil and air. The actual mode of infection by G. boninense still remains unclear. Meanwhile, some suspected cases of BSR can result from root infection, presumably following root contact with soil inoculum or other infected roots. Hence, oil palm plantations are suffering significant loss of palms at the early stages, thus directly reducing their potential oil yield. In the present study, we selected 3 isolates of G. boninense with various degree of pathogenicity (low, medium and high) which were identified through nursery trials and we cultured these isolates on two different media (carbon rich culture and carbon rich culture incorporating oil palm saw dust). The purpose of culturing isolates in the latter medium is to mimic the presence of the host tissue as compared to the former which was used as a control. Transcriptome sequencing was conducted via an Illumina platform and we investigated the expression profiles exhibited by the 3 G. boninense isolates grown under different media. We hypothesized that cell wall degradation was one of the possible modes of infection by the pathogen, hence, transcripts involved in lignin degradation process - and particularly those associated to laccase genes - were studied in detail. Concurrently, a separate analysis (not reported here) identified 33 laccase genes based on our de novo G. boninense genome assembly. All these laccase genes (de novo) contain the laccase specific four domain sequence signature encompassing cysteine and histidine residues which are involved in copper binding. Through transcriptomic analyses, in which isolates are compared under different conditions, there is no significant gene transcript detected for the isolate showing the weakest pathogenicity. Forty-five transcripts were found to be up-regulated in the G. boninense isolate with medium pathogenicity. In the most pathogenic isolate we found 409 unique transcripts which were down-regulated and 376 unique transcripts which were up-regulated and one laccase-related transcript. As we investigated further for the isolates (between medium and most pathogenic) cultivated on carbon medium supplemented with oil palm saw dust, we found that 6,551 transcripts were up-regulated (7 transcripts were found to be associated with laccase) as compared to 6,964 transcripts which were down-regulated, of which 18 transcripts were differentially expressed between two isolates cultivated on carbon medium supplemented with oil palm saw dust.